2018
DOI: 10.1007/s10126-018-9821-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Sorbicillinoid-Producing Aspergillus Strain with Antimicrobial Activity Against Staphylococcus aureus: a New Polyextremophilic Marine Fungus from Barents Sea

Abstract: The exploration of poorly studied areas of Earth can highly increase the possibility to discover novel bioactive compounds. In this study, the cultivable fraction of fungi and bacteria from Barents Sea sediments has been studied to mine new bioactive molecules with antibacterial activity against a panel of human pathogens. We isolated diverse strains of psychrophilic and halophilic bacteria and fungi from a collection of nine samples from sea sediment. Following a full bioassay-guided approach, we isolated a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…Finding the same and suitable conditions to test both microorganisms drive to set-up alternative technical procedures, like dual-media and crude extracts for testing those strains growing above the seawater salinity, ca. 3.5 % [87]. Another possible reason is that the study of extremophilic microbiota has been approached at an ecological level and the vast biotechnological exploitation of these extremophiles is more recognized on their enzymes and compatible solutes.…”
Section: Archaeamentioning
confidence: 99%
See 1 more Smart Citation
“…Finding the same and suitable conditions to test both microorganisms drive to set-up alternative technical procedures, like dual-media and crude extracts for testing those strains growing above the seawater salinity, ca. 3.5 % [87]. Another possible reason is that the study of extremophilic microbiota has been approached at an ecological level and the vast biotechnological exploitation of these extremophiles is more recognized on their enzymes and compatible solutes.…”
Section: Archaeamentioning
confidence: 99%
“…The strongest power inhibitory action was observed against Staphylococcus aureus. The molecule responsible of the activity was identified as Bisvertinolone, a compound member of the family Sorbicillinoid [87]. Aspergillus flocculosus PT05-1 and Aspergillus terreus PT06-2, both isolated from sediment of Putian sea saltern of Fujian, China, showed antimicrobial activity against Enterobacter aerogenes, Pseudomonas aeruginosa, and Candida albicans.…”
Section: Fungimentioning
confidence: 99%
“…Evidence has emerged, demonstrating that many natural products extracted from marine animals and algae are the products of associated microorganisms, mostly bacteria, and fungi (Raghukumar 2008). Spongeassociated fungi have the potential to produce new chemical entities (Volgraf et al 2008;Blunt et al 2010;Vasanthabharathi 2012;Vicente et al 2013;Bolanos et al 2015;Imhoff 2016;Indraningrat et al 2016) that actively inhibited the growths of various pathogenic microorganisms (Khoeri et al 2011;Mayer et al 2013;Radjasa et al 2013;Buttachon et al 2016;Corral et al 2018). Our previous research also showed that spongeassociated fungi have several bioactivities such as anti-S. aureus and E. coli (Wittriansyah et al 2016), antibacterial produced by sponge Agelas sp.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, the exploitation of bioactive molecules from marine origin is still scarce if compared to other natural environments [1,7], especially in the case of marine fungi [8,9]. In the last decades, the interest in marine and marine derived fungi has been growing due to their high e cacy in the synthesis of secondary metabolites [4,5,[10][11][12][13][14][15][16][17][18]. These organisms are also promising sources of enzymes useful in different technological applications [19][20][21].…”
Section: Introductionmentioning
confidence: 99%